2022
DOI: 10.3390/ph16010034
|View full text |Cite
|
Sign up to set email alerts
|

Combinatory Effect and Modes of Action of Chrysin and Bone Marrow-Derived Mesenchymal Stem Cells on Streptozotocin/Nicotinamide-Induced Diabetic Rats

Abstract: The purpose of this study was to see how chrysin and/or bone marrow-derived mesenchymal stem cells (BM-MSCs) affected streptozotocin (STZ)/nicotinamide (NA)-induced diabetic rats as an animal model of type 2 diabetes mellitus (T2DM). Male Wistar rats were given a single intraperitoneal (i.p.) injection of 60 mg STZ/kg bodyweight (bw) 15 min after an i.p. injection of NA (120 mg/kg bw) to induce T2DM. The diabetic rats were given chrysin orally at a dose of 100 mg/kg bw every other day, BM-MSCs intravenously at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Ten days postSTZ injections, rats' blood glucose concentrations were screened. Animals that fasted overnight (10–12 hours) were supplied with glucose 3 g/kg BW by oral gavage; then, 2 hours after glucose administration, blood samples were taken from the lateral tail vein, and blood glucose concentrations were measured by a glucometer obtained from Life Scan Corporation, Canada [ 23 ]. Rats having blood glucose concentrations >200 mg/dL were assigned as diabetic and selected for further biochemical, physiological, histological, and ultrastructural studies.…”
Section: Methodsmentioning
confidence: 99%
“…Ten days postSTZ injections, rats' blood glucose concentrations were screened. Animals that fasted overnight (10–12 hours) were supplied with glucose 3 g/kg BW by oral gavage; then, 2 hours after glucose administration, blood samples were taken from the lateral tail vein, and blood glucose concentrations were measured by a glucometer obtained from Life Scan Corporation, Canada [ 23 ]. Rats having blood glucose concentrations >200 mg/dL were assigned as diabetic and selected for further biochemical, physiological, histological, and ultrastructural studies.…”
Section: Methodsmentioning
confidence: 99%
“…Trypsin action was inhibited by adding 2–3 mL complete culturing medium, and cells were collected, centrifuged at 3000 rpm for 5 min in a 15 mL sterile Falcon tube, and then counted, and the viability of cells was determined via trypan blue staining [ 126 ] and examination by the inverted microscope to detect viable cells and dead cells. The identification of BM-MSCs was performed according to our previous publication [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…They are one of the earliest progenitors of stem cells to be inserted in the clinic because they reproduce widely [ 17 ], they are easy to isolate and obtain by clinical procedures based on the ability of adherence to plastic surfaces [ 18 ], and they have the potential to differentiate into multiple cell types. In our previous study, it was found that BM-MSCs alone and, in combination with the flavonoid chrysin, enhanced oral glucose tolerance via lowering inflammation, restoring β-cell functionality, and attenuating insulin resistance; the combination was the most effective treatment [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased whole blood TCD4+, TCD8+, NK cells DTH responses, total IgG, IgM production, T‐bet expression, and IFN‐γ (Zeinali et al, 2022). In the diabetic rat, it decreased C‐peptide and IL‐13 levels and increased IL‐1β and TNF‐α as well as up‐regulated activities of glucose‐6‐phosphatase and glycogen phosphorylase (Sayed et al, 2023). These data showed chrysin immunomodulatory action by targeting different immune cells.…”
Section: Immunomodulator Activity Of Several Phytoconstituentsmentioning
confidence: 99%